Porous Titanium Dioxide Spheres for Drug Delivery and Sustained Release - Cui, Xin-gang; Chen, Hua; Ye, Qing-bang; Cui, Xin-yu; Cui, Xiao-jing; Cui, Hong-jing; Shen, Guang-zhi; Li, Miao-jing; Lin, Jian-tao; Sun, Ya-xin (Frontiers in Materials, 2021)
By hydrothermal method, porous TiO2 spheres with pompon morphology are successfully synthesized in the tetrabutyl titanate (TBT)–acetic acid (HAc) system with no other additives. And the morphological, structural and textural properties of the specimen are figured out by transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), X-ray powder diffraction (XRD), N2 adsorption/desorption, and fluorescence microscope. The results show the pompon-like morphology of porous TiO2 with high specific surface area and large pore volume, which can be used as a drug carrier. In this paper, Doxorubicin hydrochloride (DOX) is chose as drug model to understand the process of drug release. And results indicate that the porous TiO2 is biocompatible and can be used for continuing drug-release, which shows lots of possibilities in medical fields.